Which Bone-Modifying Agent is Associated with Better Outcomes in Patients with Skeletal Metastases from Lung Cancer? A Systematic Review and Network Meta-analysis. Issue 9 (September 2021) - Bozzo, Anthony; Deng, Jiawen; Abbas, Umaima; Bhasin, Richa; Deodat, Marisa; Wariach, Sajid; Sanger, Stephanie; Axelrod, Daniel; Masrouha, Karim; Turcotte, Robert; Wilson, David; Ghert, Michelle
Abstract: Background: Lung cancer is one of the most commonly diagnosed cancers and is the leading cause of cancer-related deaths. Metastatic bone disease occurs in 20% to 40% of patients with lung cancer, and these patients often present with pain or skeletal-related events (SREs) that are associated with decreased survival. Bone-modifying agents such as denosumab or bisphosphonates are routinely used; however, to our knowledge, there has been no quantitative synthesis of randomized controlled trial data to determine the most effective pharmacologic treatment of metastatic bone disease because of lung cancer. Questions/purposes: We aimed to perform a network meta-analysis of randomized trials to identify the bone-modifying agent that is associated with the (1) highest overall survival, (2) longest time to SRE, (3) lowest SRE incidence, and (4) greatest likelihood of pain resolution. Methods: We conducted our study according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol and pre-registered the analysis on PROSPERO (ID: CRD42019124364). We performed a librarian-assisted search of MEDLINE, PubMed, EMBASE, Cochrane Library, and Chinese databases including China National Knowledge Infrastructure and Wanfang Data. We included randomized controlled trials reporting outcomes specifically for patients with lung cancer treated with a bisphosphonate or denosumab. SREs included pathologic fractures, spinal cord compression, hypercalcemia of malignancy, or pain resulting in surgical intervention or radiation therapy. We excluded trials exclusively reporting surrogate outcomes such as changes in bone turnover markers. Screening, data extraction, risk of bias evaluation, and Grading of Recommendations Assessment, Development, and Evaluation evaluations were performed in duplicate. We included 131 randomized controlled trials that evaluated 11, 105 patients with skeletal metastases from lung cancer. The network meta-analysis was performed using a frequentist model and the R statistical software. Results are reported as relative risks or mean differences, and the I 2 value is reported for heterogeneity. The P-score, a measure of ranking certainty that accounts for standard error, is reported for each outcome. Heterogeneity in the network was considered moderate for overall survival and time to SRE, mild for the incidence of SRE, and low for pain resolution. Results: For overall survival, denosumab was ranked above zoledronic acid and estimated to confer a mean of 3.3 months (95% CI 0.3-6.3) of increased overall survival compared with untreated patients (P-score = 89%). For the time to SRE, denosumab was ranked first with a mean of 9.1 additional SRE-free months (95% CI 6.7-11.5) compared with untreated patients (P-score = 99%), while zoledronic acid conferred an additional 4.8 SRE-free months (95% CI 3.6-6.1). Reduction in the incidence of SREs was not different between patients treated with denosumab (relative risk 0.54; 95% CI 0.33-0.87) and those treated with zoledronic acid (relative risk 0.56; 95% CI 0.46-0.67). Patients treated with the combination of ibandronate and systemic therapy were more likely to experience successful pain resolution than untreated patients (relative risk 2.4; 95% CI 1.8-3.2). Conclusion: In this comprehensive synthesis of all available randomized controlled trial evidence guiding the pharmacologic treatment of bone metastases from lung cancer, denosumab was ranked above zoledronic acid for overall survival and time to SRE and was not different for reducing the incidence of SRE. Both were superior to no treatment for each of these outcomes. Given this, we encourage physicians to consider the use of denosumab or zoledronic acid in treating this patient population. The combination of ibandronate and systemic therapy was the most effective at reducing pain because of metastases. No cost-effectiveness analysis has yet been performed for denosumab and zoledronic acid on patients with metastatic lung cancer, and this represents an avenue for future research. Level of Evidence: Level I, therapeutic study.